Determining the relationship between achievement goals and students' anxiety in statistics course with regard to the mediating role of self-efficacy - Amirgholami, Elham; Heydarei, Alireza; Askari, Parviz; Weisani, Mukhtar (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: The responsibility that the entire education system is facing today is to formulate policies and policies for the development of society in the economic, social, emotional and personality fields of individuals. Therefore, the purpose of this research was to investigate the relationship between achievement goals and students' anxiety in statistics course, considering the mediating role of self-efficacy. Methods: The current research was of the type of relational design, and more precisely, the correlation design was of the structural equation modeling type. Among the first, second, third, and fourth year students, the second and fourth year students were randomly selected, and 324 students completed the questionnaires of this research. Finally, after removing incomplete questionnaires, 312 questionnaires were analyzed. In order to collect data, achievement goals goals scale (1997), self-efficacy scale (Sherer and Adams, 1986) and Kravis et al.'s statistics anxiety scale (1985) were used as research tools in this research to collect data. In this research, SPSS19 software was used for data recording and preliminary analysis, and AMOS software was used for data analysis, and a significance level of p < 0.05 was considered for all hypotheses. Results: The results of the hypothesis analysis showed that the effect of the mediator variable in the regression model is significant and effective. As a result, the main hypothesis of the research that there is a relationship between professional ethics based on teacher's emotions and the mediating role of moral identity in teachers of Babak city is confirmed. Conclusion: It can be concluded that students' anxiety can be predicted through achievement goals with the mediation of self-efficacy.